NUMERICAL SOLUTION OF ABSORBING BOUNDARY CONDITION IN PADÉ APPROXIMATION - Mohammad Mahfuzh Shiddiq (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2015)
natural domain require an artificial boundary condition for reducing the size of its natural domain. One of these boundary conditions is absorbing boundary condition. This paper will construct an absorbing boundary condition with Padé approximations and numerical solution by finding the difference equation.